LEGAL FRAMEWORK FOR RESPONSIVE REGULATIONS SUPPORTING INNOVATION IN AN INCLUSIVE FINANCIAL SYSTEM: FOCUSING ON DATA SECURITY, INTEGRITY, AND TRUST - Endang Purwaningsih; Basrowi Basrowi (Universitas Galuh, 2025)
To strengthen the financial system, public trust is needed, continuous innovation in the financial industry, regulations that synergize with innovation leaps, and guarantees of legal certainty are the basic milestones for moving towards an inclusive financial innovation systemPurposes of the Research: This research aims to analyze problems and recommend solutions to efforts to design responsive regulations to support innovation in an inclusive financial system focusing on data security, integrity and trust, to encourage sustainable growth and community participation, and appropriate models for integrating innovation in the financial system inclusive, with a focus on aspects of data integrity, trust and security. This research is included in applied normative research, namely emphasizing secondary data supported by the results of questionnaires and interviews.Results / Main Findings / Novelty/Originality of the Research: Responsive regulations to support innovation in an inclusive financial system focus on data security, integrity and trust, to encourage sustainable growth and community participation. Regarding the issue of inclusive financial system innovation, the legal knowledge of the community and MSME actors regarding inclusive financial system innovation based on integrity and trust through data privacy policies, risk awareness and increasing literacy is at a high average. Increasing stakeholders' legal awareness, the interests of financial inclusion also need to be balanced with consumer protection. The right model for integrating innovation in an inclusive financial system relies on the implementation the Financial System Innovation Model through platform-based innovation and partnership strategies in synergy with responsive regulations